Time Delay Estimation in the Presence of Correlated Noise and Reverberation - Rui, Yong; Florencio, Dinei (ICASSP, 2004)
We propose a new two-stage framework for time delay estimation in the presence of correlated noise and reverberation. The new framework allows us to develop a set of new approaches as well as to unify existing ones. We further develop the maximum likelihood estimation when reverberation is present. The corresponding weighting function is a more accurate form of the weighting function proposed by H. Wang and P. Chu (Proc. ICASSP, 1997), one of the best existing techniques. We compare our new algorithms with the existing ones and report superior performance.